2009
DOI: 10.1111/j.1365-2559.2009.03359.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil/eosinophil‐rich type of primary cutaneous anaplastic large cell lymphoma: a clinicopathological, immunophenotypic and molecular study of nine cases

Abstract: Neutrophil/eosinophil-rich CALCL should be differentiated from various infectious and non-infectious diseases, especially from non-neoplastic cutaneous CD30+ infiltrates rich in neutrophils and eosinophils. Precise correlation of clinical presentation, morphological features, phenotypic and molecular analysis can help to establish the correct diagnosis. Whether this rare variant has a significantly different prognosis from classical CALCL needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Although the conventional variant does not have a predilection for immunocompromised individuals, the pyogenic variant is seen in those with HIV, 15 transplant recipients, 16 and hematologic malignancies including young individuals. 10,17 Microscopically, ALCL has diffuse, cohesive sheets of large pleomorphic tumor cells, strongly CD30þ, similar to ALKþ ALCL ( Figure 1). Even among the conventional variants, a rich inflammatory infiltrate is present, which can lead to a misdiagnosis of an inflammatory process in the skin.…”
Section: Lymphoproliferative Neoplasms Mature T-cell and Nk-cell Lympmentioning
confidence: 99%
“…Although the conventional variant does not have a predilection for immunocompromised individuals, the pyogenic variant is seen in those with HIV, 15 transplant recipients, 16 and hematologic malignancies including young individuals. 10,17 Microscopically, ALCL has diffuse, cohesive sheets of large pleomorphic tumor cells, strongly CD30þ, similar to ALKþ ALCL ( Figure 1). Even among the conventional variants, a rich inflammatory infiltrate is present, which can lead to a misdiagnosis of an inflammatory process in the skin.…”
Section: Lymphoproliferative Neoplasms Mature T-cell and Nk-cell Lympmentioning
confidence: 99%
“…Of these 11 cases, 5 also lacked CD4 and CD8 expression. 7,9,[21][22][23][24][25][26] Only 1 of our CD4 2 / CD8 2 cases expressed TIA-1, demonstrating that most of these double-negative cases do not express a cytotoxic phenotype. Although several studies reported on loss of T-cell markers expression, detailed phenotypic aberrations and loss of all T-cell markers were never described.…”
Section: Discussionmentioning
confidence: 99%
“…Both solid tumors and hematopoietic neoplasms are associated with eosinophilia. Eosinophilia and tissue eosinophilia are frequent findings in Hodgkin lymphoma [ 25 ] and are sometimes observed in patients with lymphoma, predominantly T cell lymphoma or occasionally anaplastic large cell lymphoma [ 26 , 27 ]. Historically, large B cell lymphoma with marked eosinophilia is rare, and only a few cases of mediastinal/thymic large B cell lymphoma may present a few reactive infiltrating lymphocytes and eosinophils.…”
Section: Discussionmentioning
confidence: 99%